Acromion, coracoid and glenoid processes of scapula: an anatomical study - Nayak, Gyanaranjan; Panda, Sitansu K.; Chinara, Prafulla K. (International Journal of Research in Medical Sciences, 2020)
Background: Acromion morphology has an important role in impingement syndrome and pathogenesis of rotator cuff diseases. Coracoid process is involved in many surgical procedures of shoulder joint. Dimensions of glenoid process are essential in designing glenoid components for total shoulder replacement. Aim of the study was to measure the various dimensions and note the morphology of acromion, coracoid and glenoid processes of scapula. Methods: Fourty two scapulae (24 right, 18 left) were used and the dimensions of the three processes were measured with digital Vernier calipers. Results: The findings were as follows- length of acromion- 43.57±5.13 mm; width of acromion- 25.03±3.57 mm; acromio-coracoid distance- 33.09±7.02 mm; acromio-glenoid distance- 25.24±4.05 mm; height of coraco-acromial arch- 15.17±3.8 mm; length of coracoid- 38.73±3.72 mm; width of coracoid- 14.28±2.36 mm; tip thickness of coracoid- 8.61±1.89 mm; height of base coracoid- 12.91±2.88 mm; width of base of coracoid- 22.31±3.54 mm; height of glenoid- 34.18±3.53 mm; superior antero-posterior glenoid length- 15.35±2.35 mm and inferior antero-posterior glenoid length- 23.9±2.52 mm. Conclusions: The results will be highly relevant in orthopaedic surgery and manufacturing shoulder prosthesis.